2022
DOI: 10.9734/psij/2022/v26i7752
|View full text |Cite
|
Sign up to set email alerts
|

Computational Nanomaterials Design: towards the Realization of Nanoparticle use in Radiotherapy Case Study 2: Adsorption states of At on Au (111) Surface

Abstract: Astatine-211 (211At or simply At) used as an α particle emitter is currently gaining as treatment method for cancer cells. It must however be attached to a carrier to facilitate the treatment process. Gold nanoparticle is a good candidate that has been used in several tests. Knowing the physics behind the adsorption of astatine on gold nanoparticles would be advantageous in designing a more optimal method for such applications. We therefore performed density functional theory calculation on astatine adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…30 and experiment, 33 to "obvious limitations" of the cluster model, the neglect of cluster relaxation caused by adsorption, and the use of the DFT model without a dispersion correction. However, Tanudji et al, 31 whose results are also much closer to the experiment than those in ref. 32, evaluate the dispersion contribution to the At -Au (111) adsorption energy at ca.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…30 and experiment, 33 to "obvious limitations" of the cluster model, the neglect of cluster relaxation caused by adsorption, and the use of the DFT model without a dispersion correction. However, Tanudji et al, 31 whose results are also much closer to the experiment than those in ref. 32, evaluate the dispersion contribution to the At -Au (111) adsorption energy at ca.…”
Section: Introductionsupporting
confidence: 59%
“…To address significant discrepancies in theoretical At-Au(111) binding energies estimates [30][31][32] attributed by Ryzhkov et al 32 to possible shortcomings of the cluster model used in ref. 30, we first address the potential effects of Au(111) relaxation.…”
Section: Adsorption Of Atomic Astatinementioning
confidence: 99%
See 1 more Smart Citation
“…The integration for the first Brillouin zone was performed by a mesh of 5 × 5 × 1 k-points with a Monkhorst-Pack sampling scheme [18]. Finally, van der Waals (vdW) calculations employed the DFT-D3 code developed by Grimme et al [19], based on findings of previous works which showed vdW-incorporated calculations' results bring closer to the results obtained in experiments [13].…”
Section: Methodsmentioning
confidence: 97%
“…CMD ® techniques are also used in the study on biosynthesis of melanin pigment, where the understanding of how melanin is formed contributed to the development of more effective protective agents [11]. Our previous works using CMD ® have found that both iodine and astatine can be adsorbed on Au(111) surface by covalent bonding [12,13]. The choice for such facet is based on the premise that a larger AuNP would have more flat surfaces than edges.…”
Section: Introductionmentioning
confidence: 99%